(untitled) (Perner’s Contacts, 2020)
This paper deals with the problematics of tensile testing of maraging steel lightweight cylindrical samples with internal structures, intended for automotive application. The samples were made with DMLS technology and tensile tested under the static strain rate of 0.002 s-1. During the loading, uneven deformations and multiple necking occurred on the samples. The mentioned effect significantly affects the state of stress and deformation at the final fracture zone, as well as the total deformation into the fracture, which means that it actually distorts the standard tensile test record. Therefore, a methodology for capturing the deformation response using the ARAMIS optical system was proposed. The methodology is presented and verified by a set of experiments for BCC internal structure.